IDENTIFIKASI ARKEOLOGI SARANA DAN PRASARANA MAHAVIHARA MUARAJAMBI SEBAGAI PUSAT PENDIDIKAN DI ASIA TENGGARA PADA MASA MELAYU KUNO ABAD VII-XII: Identification of Archeology Mahavihara Muarajambi Facilities and Infrastructures As a Central Education In Southeast Asia In Malay Ancient Time of The VII-XII Century - Asyhadi Mufsi Sadzali (BALAI ARKEOLOGI PAPUA, 2020)
An Identification of Archeology Mahavihara Muarajambi Facilities and Infrastructures As a Central Education In Southeast Asia In Malay Ancient Time Of The VII-XII CenturyBy;Asyhadi Mufsi Sadzali, Yundi Fitrah Abstract: The development of Buddhism in Sumatra, especially in Jambi, has been going on since at least the 7th century, as evidenced by archaeological remains in the form of the distribution of temple structures in an area of ??3,900 hectares. Reconstruction efforts have been carried out since 1975, until now, but the interpretation of the functions of the buildings in the MuaraJambi temple area has not been studied much, so it is always associated with religious worship buildings. These assumptions will be expressed through two research questions; 1. What were the kinds of archaeological data supporting the MuaraJambi temple as an educational centre 2. How were the educational support facilities found in the Muarajambi Temple in the 7th-12th century AD. Disclosure of research questions using archaeological methods, through systematic stages including; collecting data, processing data in the form of identification and classification, and interpreting data. In the final section, it would discuss the function of each temple building and other supporting structures, namely as a means of educational infrastructure in Southeast Asia1in VII-XII AD century.Keywords: Mahavihara, Temple, Muarajambi IDENTIFIKASI ARKEOLOGI SARANA DAN PRASARANA MAHAVIHARA MUARAJAMBI SEBAGAI PUSAT PENDIDIKAN DI ASIA TENGGARA PADA MASA MELAYU KUNO ABAD VII-XII Oleh; Asyhadi Mufsi Sadzali, Yundi Fitrah abstrak: perkembangan ajaran Buddha di Sumatera, khususnya di Jambi telah berlangsung setidaknya sejak abad ke-7, dibuktikan dengan tinggalan arkeologi berupa sebaran struktur candi di kawasan Percandian Muarajambi seluas 3.900 Ha. Upaya rekonstruksi telah dilakukan sejak tahun 1975, namun interpretasi fungsi bangunan belum banyak diteliti, sehingga hanya dikaitkan dengan bangunan peribadatan agama Buddha. Akantetapi perkembangan data penelitian menunjukkan hal berbeda, ada kemungkinan fungsi lain, yakni sebagai pusat pendidikan. Asumsi tersebut diungkapkan melalui dua pertanyaan penelitian; Apa saja ragam data arkeologi pendukung percandian Muarajambi sebagai pusat pendidikan? Bagaimana sarana-prasarana pendukung pendidikan di Percandian Muarajambi pada abad ke-7 -12 M? Untuk menjawab pertanyaan penelitian digunakan metode arkeologi, melalui tahapan sistimatis meliputi; pengumpulan data, pengolahan data dalam betuk identifikasi dan klasifikasi, serta interpretasi data. Pada bagian ahir diambil kesimpulan terkait fungsi masing-masing bangunan candi serta struktur pendukung lain sebagai sarana prasarana pendidikan di Asia Tenggara pada abad ke-7 – 12 M. Kata kunci: Mahavihara, Candi, Muarajambi